(3GdTgGH GdKGbH aj efGbH GdEeGe Ydi Hf CHj WGdHs - (3CHh GdMSf CMeO Hf eMeO Hf GdMSf Hf eMeO GdQUGU,J (B565 (3g` s ((3eMeO Hf bGSe Hf SdjeGf Hf eMeO GdNjGW s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ef YdjfG HGdESdGe CMHHJ Cf CPcQ ai gPG dGeNJUQ LedI ef aVGFd Ydi efgG eGgh eJhGJQhefgG eGgh ai Mce GdeJhGJQ cd Pdc HGdCSGfjO s
(3BNQgG (B:s
(3bGd GdTGYQi JYUi GdEdg hCfJ JXgQ MHg gPG eMGd ai GdebGd HOjY gjgGJ dh CMHHJg dCWYJg Efg GdeMH def jMH jWjY GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs